Fertilizer subsidies in Africa: Are vouchers the answer? - Minot, Nicholas; Benson, Todd (International Food Policy Research Institute, 2009)
In the 1970s and 1980s, most African countries sold fertilizer at subsidized prices through state-owned enterprises. In response to the fiscal cost and ineffective implementation of these subsidies, as well as pressure from international financial institutions, almost all of these countries liberalized their fertilizer markets to some degree as part of structural adjustment programs carried out in the late 1980s and early 1990s. Under these reforms, governments eliminated state monopolies on fertilizer distribution and phased out universal subsidies.